Oxygen-based microwave induced plasma etching for epoxy molding compound removal in advanced semiconductor devices - Tan, Hong Siang (2025)
Heterogenous integration has led to the development of advanced semiconductor packages with better performance and smaller form factor. Such packages usually comprise of multiple dies and embedded components which are encapsulated with epoxy molding compounds (EMCs) to improve the reliability performance and to protect the die from external impact. However, this increases the difficulty of failure analysis (FA) as the defects may manifest in the embedded components that are covered by EMCs. Suitable sample preparation techniques and workflows are required to remove EMCs to reveal the defects to determine the root cause of failure. This paper explores the use of microwave induced plasma (MIP) etcher to remove EMCs. Tool parameters are varied to understand their effects on the removal rate of EMCs such as underfill.